Investigation and analysis of knowledge and perceptions on tuberculosis prevention and control among university students in Chengdu, China - Khalaf, Ahmad Taha; Jun, Wan; Xiaoming, Liu; Mohd Desa, Mohd Nasir; Yusuf, Ahmad; Ramli, Noraasyikin (Universidad Tecnica de Manabi, 2022)
To explore Tuberculosis (TB) health promotion and education in universities, and to provide a feasible reference method and specific implementation measures for improving health education among university students. We collected a total of 811 respondents, using a uniform questionnaire online survey questionnaire network. The completed questionnaires were double-entered using EpiData3.1, the database was established, and the analysis was performed by Excel2016 and SPSS 22 software. The total awareness rate of the 8 core information on tuberculosis prevention and control was 74.2 %. Among them, “the state provides free anti-tuberculosis drugs and major tests for infectious tuberculosis patients” with the lowest awareness rate of 49.2 %; followed by the awareness rate of “should care about tuberculosis patients and should not discriminate against tuberculosis patients”, for 63.8 %. The channels for college students to acquire knowledge about tuberculosis prevention were “newspapers and magazines”, accounted for 50.3 percent; “broadcasting, television and video” accounted for 52.4 %; “wall advertising, bulletin boards, slogans” accounted for 44.6 %; “School Health Education” accounted for 38.5 % of “school propaganda columns or publicity panels” accounted for 34.9 %. The favourite way for college students to promote was “watching TV” 40.3 %. In conclusion, the awareness rate of TB prevention and control knowledge among students at Chengdu University was low, and the health education of tuberculosis in colleges and universities still needs to be strengthened.